O estudo da equação de Dirac no espaço curvo na métrica de Schwarzschild. - Ferreira, Wesllen Hammet Rupf (2020)
This work presents the study of the reasons for the need for the introduction of gravitation, General Relativity, whose foundation is based on Differential Geometry, together with theories that describe matter. We are going to establish the objects of thi